2021
DOI: 10.1038/s41598-021-83410-x
|View full text |Cite
|
Sign up to set email alerts
|

Composite cardiovascular risk and BMI affected comparative profiles of BIAsp 30 + metformin vs BIAsp 30 monotherapy: a MERIT post-hoc analysis

Abstract: We assessed whether comparative efficacy and safety of biphasic insulin aspart 30 (BIAsp 30) plus metformin versus BIAsp 30 monotherapy differed for patients with type 2 diabetes mellitus (T2DM) inadequately controlled with oral antidiabetic drugs with different cardiovascular risk scores and different body mass indexes (BMI) by performing a post hoc analysis of the randomized controlled MERIT study. In the MERIT study, eligible patients were randomized 1:1 to receive BIAsp 30 plus metformin or BIAsp 30 for 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Metformin(Met) is the first-line drug for the treatment of T2DM and plays an anti-hyperglycemic role mainly by inhibiting liver glucose through AMPK-dependent or -independent pathways (11)(12)(13)(14). The Chinese MERIT study showed that premixed insulin combined with Met resulted in a greater reduction in HbA1c, less insulin consumption, less weight gain, a lower incidence of hypoglycemia, and lower cardiovascular risk than premixed insulin alone (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Metformin(Met) is the first-line drug for the treatment of T2DM and plays an anti-hyperglycemic role mainly by inhibiting liver glucose through AMPK-dependent or -independent pathways (11)(12)(13)(14). The Chinese MERIT study showed that premixed insulin combined with Met resulted in a greater reduction in HbA1c, less insulin consumption, less weight gain, a lower incidence of hypoglycemia, and lower cardiovascular risk than premixed insulin alone (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%